2014
DOI: 10.1111/febs.12905
|View full text |Cite
|
Sign up to set email alerts
|

Sestrin2 promotes Unc‐51‐like kinase 1 mediated phosphorylation of p62/sequestosome‐1

Abstract: Autophagy is a homeostatic process that is important for degrading protein aggregates, nutrient deposits, dysfunctional organelles and several signaling molecules. p62/sequestosome-1 is a protein that binds to several autophagy substrates, such as ubiquitinated proteins, damaged mitochondria and signaling molecules such as an Nrf2 inhibitor Keap1, promoting their autophagic degradation. Sestrin2, a stress-inducible protein, has been recently shown to bind to p62 and promote autophagic degradation of such p62 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 44 publications
7
81
0
Order By: Relevance
“…29 In a recent study, SESN2 was shown to also induce autophagic degradation of SQSTM1 by promoting ULK1-mediated SQSTM1 phosphorylation via its interaction with ULK1 and SQSTM1. 38 Based on these data and our result that SESN2 induces mitophagy by mediating SQSTM1 binding to ubiquitinated mitochondria via its interaction with SQSTM1, we speculate that SESN2 may be involved in SQSTM1-mediated autophagic degradation through its binding to SQSTM1 and/or SQSTM1 target proteins in response to various cellular stresses. Although we did not identify any Lys63 ubiquitinated proteins on the mitochondrial surface which interacted with SESN2 or SQSTM1, we suggest that SESN2 functions as a scaffold protein that strengthens the otherwise weak association of SQSTM1 with ubiquitinated proteins on mitochondria, resulting in mitophagy.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…29 In a recent study, SESN2 was shown to also induce autophagic degradation of SQSTM1 by promoting ULK1-mediated SQSTM1 phosphorylation via its interaction with ULK1 and SQSTM1. 38 Based on these data and our result that SESN2 induces mitophagy by mediating SQSTM1 binding to ubiquitinated mitochondria via its interaction with SQSTM1, we speculate that SESN2 may be involved in SQSTM1-mediated autophagic degradation through its binding to SQSTM1 and/or SQSTM1 target proteins in response to various cellular stresses. Although we did not identify any Lys63 ubiquitinated proteins on the mitochondrial surface which interacted with SESN2 or SQSTM1, we suggest that SESN2 functions as a scaffold protein that strengthens the otherwise weak association of SQSTM1 with ubiquitinated proteins on mitochondria, resulting in mitophagy.…”
Section: Discussionsupporting
confidence: 59%
“…29,38 Several studies have revealed that signal-dependent phosphorylation of SQSTM1 at specific sites (Ser349, Ser351, Ser403) is critical to degradation of ubiquitinated proteins targeted by SQSTM1 by reinforcing interactions between them. 29,39,40 Therefore, we first examined the extent of phosphorylation of SQSTM1 at Ser349, Ser351, and Ser403 in Sesn2 C/C BMDMs in the absence or presence of stimulation.…”
Section: Sesn2 Induces Mitochondrial Priming By Facilitating Perinuclmentioning
confidence: 99%
“…Increasing evidence demonstrates that the autophagy receptor protein p62/SQSTM1 is mainly mediated through ULK1 in response to energetic stress [45]. In addition, it is known that AKT regulates ULK1 during the process of autophagy, which is also regulated by AMPK [18,20].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed Ad-Sesn2 directly increased LC3-II expression and that eupatilin-mediated LC3-II expression was abolished by si-Sesn2, which also support the notion that Sesn2 activates autophagy. Recently, Ro et al [48] suggested that Sesn2 directly promotes ULK1-dependent autophagic degradation. In accordance with these studies, our supplemental data showed that Ad-Sesn2 promoted the phosphorylations of AMPKa and ULK1.…”
Section: Discussionmentioning
confidence: 99%